"What does it matter?" Young sexual minority men discuss their conversations with sexual partners about HPV vaccination. Issue 2 (12th February 2023) - Malone, Molly A.; Gower, Amy L.; Reiter, Paul L.; Kiss, Dale E.; McRee, Annie-Laurie
Abstract: Objective: Human papillomavirus vaccination coverage is suboptimal, especially among males. Social networks influence young adults' health behaviors and could be leveraged to promote vaccination. We sought to describe how young sexual minority men communicate about human papillomavirus (HPV) vaccination with their sexual partners. Participants: National (U.S.) sample of sexual minority men ages 18–26 ( n  = 42) from January 2019. Methods: We conducted four online focus groups and identified salient themes using inductive content analysis. Results: Across groups, participants described that HPV vaccination is not a focus of their conversations with sexual partners. Other key themes related to HPV vaccine communication included: varying discissions based on relationship type, and valuing conversations with partners about safer sex. Conclusions: Findings provide novel insight into how young sexual minority men communicate with their sexual partners about HPV vaccination and identify potential areas for interventions to promote communication. Future research is needed to investigate associations between partner communication and HPV vaccine uptake.